Employment of advanced oxidation processes in the degradation of a textile dye mixture: evaluation of reaction parameters, kinetic study, toxicity and modeling by artificial neural networks - Oliveira, Marcos André Soares de; Neves, Naiana Santos da Cruz Santana; Santana, Rayany Magali da Rocha; Lucena, Alex Leandro Andrade de; Zaidan, Léa Elias Mendes Carneiro; Cavalcanti, Vanessa De Oliveira Marques; Silva, Gilson Lima da; Napoleão, Daniella Carla (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Organic contaminants in industrial effluents threaten the quality of water resources, especially due to their resistance to natural degradation. The textile industry gain relevance, considering that it generates large volumes. This work aimed to evaluate the efficiency of different advanced oxidation processes (AOP) for the degradation of the mixture textile dyes in solution. After optimization of the main parameters involved in the applied processes and systems, the AOP with greater efficiency in the degradation of the compounds was the photo-Fenton/UV-C (92%) after 360 min of treatment. The experimental data showed a better fit to the Chan and Chu kinetic model and trough an evaluation using artificial neural networks it was possible to predict the maximum degradation achievable by the dye mixture. The toxicity assays, using multiple species of seeds indicated a treated solution with no toxic effects and that the applied methodology can be used without affecting the water resources.